2015
DOI: 10.18632/oncotarget.5782
|View full text |Cite
|
Sign up to set email alerts
|

ALDH/CD44 identifies uniquely tumorigenic cancer stem cells in salivary gland mucoepidermoid carcinomas

Abstract: Collectively, these data demonstrate that salivary gland mucoepidermoid carcinomas contain a small population of cancer stem cells with enhanced tumorigenic potential and that are characterized by high ALDH activity and CD44 expression. These results suggest that patients with mucoepidermoid carcinoma might benefit from therapies that ablate these highly tumorigenic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 51 publications
5
68
0
2
Order By: Relevance
“…Tumor cell lines derived from primary and metastatic MEC were established in the Nör laboratory at the University of Michigan [26, 30]. We examined histone H3 acetylation in 5 MEC cell lines, including UM-HMC1, UM-HMC2, UM-HMC3A, UM-HMC3B, and UM-HMC5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cell lines derived from primary and metastatic MEC were established in the Nör laboratory at the University of Michigan [26, 30]. We examined histone H3 acetylation in 5 MEC cell lines, including UM-HMC1, UM-HMC2, UM-HMC3A, UM-HMC3B, and UM-HMC5.…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in MEC biology have occurred through the identification of a subpopulation of CSCs with high tumorigenic properties [26]. However, the role of CSCs in chemoresistance in MEC is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that ALDH activity and CD44 expression can be used to identify cancer stem cells (CSC) in salivary gland tumors (2326). To elucidate the impact of MI-773 and/or Cisplatin treatment on ACC cancer stem cells, mice harboring UM-HACC-PDX-5 tumors were divided in 4 groups (n=5) and received MI-773 (200 mg/kg) for one week, combined or not with two single doses of Cisplatin (at the 1 st and 7 th day) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Salivary gland cancer stem cells were identified as ALDH high CD44 high cells, as previously described (25,26). UM-PDX-HACC-5 tumors were collected, cut in small pieces, and dissociated using the GentleMACS dissociator kit (Miltenyi Biotec), incubated in ACK red blood cell lysis buffer (Invitrogen), and filtered through a 40-µm sterile cell strainer.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Adams and co-workers have shown that MEC have a small fraction of cells with high tumourigenic potential (17). ALDH high /CD44 high cells isolated from MEC showed higher ability to form primary and secondary salispheres in vitro when compared to ALDH low / CD44 low cells as well as generate MEC in vivo characterized by abundant intermediate-like cells, with spindle shape, oval nuclei and highly anaplastic areas.…”
Section: Introductionmentioning
confidence: 99%